Ibrutinib plus obinutuzumab versus chlorambucil plus obinutuzumab in first-line treatment of chronic lymphocytic leukaemia (iLLUMINATE): a multicentre, randomised, open-label, phase 3 trial. Issue 1 (January 2019) - Moreno, Carol; Greil, Richard; Demirkan, Fatih; Tedeschi, Alessandra; Anz, Bertrand; Larratt, Loree; Simkovic, Martin; Samoilova, Olga; Novak, Jan; Ben-Yehuda, Dina; Strugov, Vladimir; Gill, Devinder; et al.
Summary: Background: Both single-agent ibrutinib and chlorambucil plus obinutuzumab have shown superior efficacy to chlorambucil monotherapy and are standard first-line treatments in chronic lymphocytic leukaemia. We compared the efficacy of the combination of ibrutinib plus obinutuzumab with chlorambucil plus obinutuzumab in first-line chronic lymphocytic leukaemia or small lymphocytic lymphoma. Methods: iLLUMINATE is a multicentre, randomised, open-label, phase 3 trial done at 74 academic and community hospitals in Australia, Canada, Israel, New Zealand, Russia, Turkey, the EU, and the USA in patients with previously untreated chronic lymphocytic leukaemia or small lymphocytic lymphoma, either aged 65 years or older or younger than 65 years with coexisting conditions. Patients were randomly assigned (1:1) using a blocked randomisation schedule, stratified by Eastern Cooperative Oncology Group performance status and cytogenetics, to receive ibrutinib plus obinutuzumab (oral ibrutinib [420 mg once daily continuously] combined with intravenous obinutuzumab [100 mg on day 1, 900 mg on day 2, 1000 mg on day 8, and 1000 mg on day 15 of cycle 1 and on day 1 of subsequent 28-day cycles, for a total of six cycles]) or chlorambucil plus obinutuzumab (oral chlorambucil [0·5 mg/kg bodyweight on days 1 and 15 of each 28-day cycle for six cycles] combined with the same obinutuzumab regimen). Allocation concealment was achieved using an interactive web response system. Patients and investigators were not masked to treatment assignment. The primary endpoint was progression-free survival assessed by a masked independent review committee in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of study treatment. This study is registered withClinicalTrials.gov (NCT02264574 ), and patient enrolment is complete. Findings: Between Oct 6, 2014, and Oct 12, 2015, 229 patients were enrolled and randomly assigned to receive ibrutinib plus obinutuzumab (n=113) or chlorambucil plus obinutuzumab (n=116). After a median follow-up of 31·3 months (IQR 29·4–33·2), median progression-free survival was significantly longer in the ibrutinib plus obinutuzumab group (median not reached [95% CI 33·6–non-estimable]) than in the chlorambucil plus obinutuzumab group (19·0 months [15·1–22·1]; hazard ratio 0·23; 95% CI 0·15–0·37; p<0·0001). Estimated 30-month progression-free survival was 79% (95% CI 70–85) in the ibrutinib plus obinutuzumab group and 31% (23–40) in the chlorambucil plus obinutuzumab group. The most common grade 3 or 4 adverse events in both groups were neutropenia and thrombocytopenia. Serious adverse events occurred in 65 (58%) of 113 patients treated with ibrutinib plus obinutuzumab and 40 (35%) of 115 patients treated with chlorambucil plus obinutuzumab. Ibrutinib or chlorambucil treatment-related deaths were reported in one (1%) of 113 patients in the ibrutinib plus obinutuzumab group (sudden death) and one (1%) of 115 patients in the chlorambucil plus obinutuzumab group (neuroendocrine carcinoma of the skin). Interpretation: Ibrutinib plus obinutuzumab is an efficacious and safe chemotherapy-free combination treatment in previously untreated patients with chronic lymphocytic leukaemia or small lymphocytic lymphoma independent of high-risk features and provides an alternative first-line treatment option for these patients. Funding: Pharmacyclics LLC, an AbbVie Company, and Janssen Research and Development.